2013
DOI: 10.1038/ki.2013.219
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic GMP–dependent protein kinase Iα suppresses kidney fibrosis

Abstract: Cyclic guanosine monophosphate (cGMP) is synthesized by nitric oxide or natriuretic peptide-stimulated guanylyl cyclases and exhibits pleiotropic regulatory functions in the kidney. Hence, integration of cGMP signaling by cGMP-dependent protein kinases (cGKs) might play a critical role in renal physiology; however, detailed renal localization of cGKs is still lacking. Here, we performed an immunohistochemical analysis of cGKIα and cGKIβ isozymes in the mouse kidney and found both in arterioles, the mesangium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 37 publications
6
34
1
Order By: Relevance
“…PKG-I also protected against cisplatin-induced acute kidney injury by preserving mitochondria function (17) and prevented the development of diabetic renal complications by inhibiting high-glucose-induced thrombospondin 1-dependent TGF-␤ activity (29). In the present study, we revealed another important protective role of PKG-I in renal fibrosis induced by UUO, which is in agreement with a recent study from Schinner et al (23). By using both genetic and pharmacological approaches, the anti-fibrotic effect of PKG-I was further confirmed in this study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…PKG-I also protected against cisplatin-induced acute kidney injury by preserving mitochondria function (17) and prevented the development of diabetic renal complications by inhibiting high-glucose-induced thrombospondin 1-dependent TGF-␤ activity (29). In the present study, we revealed another important protective role of PKG-I in renal fibrosis induced by UUO, which is in agreement with a recent study from Schinner et al (23). By using both genetic and pharmacological approaches, the anti-fibrotic effect of PKG-I was further confirmed in this study.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to protecting against acute kidney injury, we also found that increasing PKG activity inhibited high glucose-induced thrombospondin 1-dependent transforming growth factor (TGF)-␤ activity and prevented ECM accumulation in kidney mesangial cells, suggesting an anti-fibrotic effect of PKG-I in chronic kidney disease, e.g., diabetic renal complications (29). Importantly, this concept is supported by a recent study showing that treatment with the guanylyl cyclase activator or NO donor (isosorbide dinitrate) suppresses renal fibrosis via PKG-I (23). Taken together, these studies strongly suggest the therapeutic potential of increasing PKG activity in treating renal fibrosis.…”
mentioning
confidence: 90%
“…In this study, prolonged cold ischemic injury resulted in a significant loss of renal function, increased tubular injury, higher levels of inflammation, and reduced levels of urinary cGMP. Cyclic GMP can also be stimulated by natriuretic peptides which may also have some involvement (16). Nitric oxide donors can be beneficial during reperfusion by compensating for reduced bioavailability of NO after ischemic injury but are limited by their rapid release and potential toxic side effects (15).…”
Section: Discussionmentioning
confidence: 99%
“…This compound was subsequently characterized as a direct NO-independent, but heme-dependent, sGC stimulator [10,25]. Kidney fibrosis induced by unilateral ureter ligation was inhibited by YC-1 via activation of cGMP-dependent protein kinase I [26]. However, along with its relatively weak sGC stimulating potency, it revealed a poor pharmacokinetic profile and a lack of specificity, as it was found to inhibit phosphodiesterases and to modulate many cGMP-independent effects [27].…”
Section: Sgc Stimulatorsmentioning
confidence: 98%